ISOLATED HARD PHOTON-EMISSION IN HADRONIC Z0 DECAYS - Adriani, O; Aguilarbenitez, M; Ahlen, S; Akbari, H; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; et al. (1992)
We report on a study of energetic, isolated photons in a sample of ∼ 320 000 Z0 hadronic decays. Energetic isolated photons probe the short-distance structure of QCD. We compare our data with the prediction of several QCD-based calculations. A search for new processes with one or two photons in the hadronic final state is also presented. No evidence for physics beyond the standard model is found. © 1992.